Study on X-ray fluorescence measurement method for Fe content in secondary circuit sampling filter membranes of nuclear power plants - Yu Zhang; Jin-Zhe Zhang; Hong-Yu Chen (International Journal of Advanced Nuclear Reactor Design and Technology)
The measurement of iron (Fe) content in second-loop sampling filter membranes is critical for evaluating corrosion product deposition in pressurized water reactor (PWR) nuclear power plants. Traditional atomic absorption spectrometry (AAS) methods face challenges such as long prolonged analysis cycles, high operational complexity, and safety risks associated with acid digestion. This study proposes a rapid and non-destructive X-ray fluorescence (XRF) method as an alternative. Standard filter membranes were prepared using Fe2O3 and Fe3O4 oxides via vacuum filtration, and a calibration curve was established for XRF quantification. Results demonstrated a strong linear correlation (R2 > 0.99) between XRF and AAS measurements, with XRF achieving a lower detection limit (0.51 μg/cm2 vs. 4.91 μg/cm2). Statistical analysis confirmed that XRF meets quantitative accuracy criteria (R2 = 0.98–0.99) for Fe content analysis in plant filter membranes. The method's feasibility is further validated by addressing matrix effects from oxide morphology and moisture interference. This work provides a reliable approach for real-time monitoring of corrosion products in nuclear systems, reducing reliance on hazardous acid digestion processes.